2007
DOI: 10.1002/adfm.200700254
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Superconducting Property Variations with Nominal Mg Non‐Stoichiometry in MgxB2 and Its Enhancement of Upper Critical Field

Abstract: By applying a combination of characterisation tools, changes in structural and superconducting properties with nominal Mg non‐stoichiometry in MgxB2 are found. The non‐stoichiometry produces enhanced in‐field critical current densities (Jc's) and upper critical field / irreversibility field (Hc2/Hirr(T)) values. Upper critical fields of ∼ 21 T (4.2 K) were obtained in nominal Mg‐deficient samples compared to ∼ 17 T (4.2 K) for near‐stoichiometric samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 40 publications
7
20
0
Order By: Relevance
“…Fig.4 shows the normalized resistivity plots three representative samples BM500, BM100 and BM30 corresponding to the highest, intermediate and lowest particle size of Mg precursor. The data is in concurrence with the reported results [12] for the MgB 2 bulk samples that are prepared by varying Mg:B ratio. The sample with larger Mg precursor size has more temperature dependence of resistivity as compared to the sample with smaller Mg precursor size.…”
Section: Cross Sectional Fe-sem Morphologysupporting
confidence: 91%
See 1 more Smart Citation
“…Fig.4 shows the normalized resistivity plots three representative samples BM500, BM100 and BM30 corresponding to the highest, intermediate and lowest particle size of Mg precursor. The data is in concurrence with the reported results [12] for the MgB 2 bulk samples that are prepared by varying Mg:B ratio. The sample with larger Mg precursor size has more temperature dependence of resistivity as compared to the sample with smaller Mg precursor size.…”
Section: Cross Sectional Fe-sem Morphologysupporting
confidence: 91%
“…(f)) BM500 along with the presence of large pore like opening again stresses upon the effects of larger Mg particle size of precursor. Since there was no evidence of any significant peak of Mg in the XRD for BM500, the presence of excessive metallic Mg can be negated, which can be explained by the possibility of quick evaporation of liquid Mg [12] during the reaction leaving behind pore like openings. Nevertheless the possibility of XRD-blind Mg traces cannot be completely ruled out.…”
Section: Cross Sectional Fe-sem Morphologymentioning
confidence: 97%
“…Indeed, recent point contact Andreev reflection measurements of polycrystalline samples [25] reveal that deliberately introducing Mg deficiency dirties the π band without introducing significant interband scattering. Earlier investigations performed on the same samples [26] also found that T c remains constant across the sample series. These observations agree with our results.…”
mentioning
confidence: 52%
“…Meanwhile, in case of samples with Mg ambiance, the resistivity shows much improved power law dependence in temperature with a reduced transition width of 1 K. This can indicate the increased dependence on electron-phonon scattering due to the decrease in defect and improved intra-grain as well as inter-grain connectivity [18]. Further, it can be observed that the actual superconducting current carrying fraction is much higher for ArMg sample as compared to ArHMg sample.…”
Section: Resistivity Behaviormentioning
confidence: 90%
“…From inset it can be easily understood that the overall resistivity decreases from Ar to ArH sample, while it is highly reduced for the samples annealed with Mg ambiance. The values for effective current carrying area, A f calculated using Rowell analysis [17][18], onset (T c, on ), offset (T c, off ) and width (∆T c ) of the superconducting transition is given in table 1. The decrease in the resistivity of ArH samples supports our argument of H 2 with some reducing effect, which more or less cleans the grain as well as the grain boundary from the oxides rendering the improved overall connectivity and hence the reduced resistivity.…”
Section: X-ray Diffraction Studiesmentioning
confidence: 99%